ISOLASI BAKTERI DARI TANAH TEMPAT PEMBANGAN AKHIR (TPA) AIR SEBAKUL SEBAGAI AGEN BIODEGRADASI LIMBAH PLASTIK POLYETHYLENE - Desy Purnama Sari; Hermansyah Amir; Rina Elvia (University of Bengkulu, 2020)
This study aims to obtain the bacteria of Pseudomonas from the land of TPA Air Sebakul Bengkulu City as a plastic degrading agent and measure the ability of bacteria to degrade Low Density Polyethylene (LDPE) and Oxium plastic. The research was conducted from February to August 2019, at the Laboratory of Biology and Chemistry Learning, Faculty of Teacher Training and Education, University of Bengkulu. Air Sebakul landfill samples were taken at the coordinate point 3o49 '27.8